PENGARUH MEDIA AUDIO VISUAL TERHADAP SIKAP KECANDUAN MEROKOK PADA SISWA KELAS X DI SMK NEGERI 1 JONGGAT TAHUN PELAJARAN 2021/2022 - Mamat, Masajidi; Mujiburrahman, Mujiburrahman (Program Studi Pendidikan Luar Sekolah, 2022)
Abstract:Adolescents as the target of health education counseling about the dangers of smoking, based on the assumption that psychologically the personality characteristics of adolescents are unstable. The formula of the problem in this research is how much Influence Of Audio Visual Media On Smoking Addiction Attitudes in Class X Students in SMKN 1 Jonggat School Year 2021/2022? The purpose of this study was to find out the Effect of Audio Visual Media on Smoking Addiction Attitudes in Class X Students in SMKN 1 Jonggat School Year 2021/2022. The population in this study was 109 while the sample in this study was 17 with the data collection method used as the main method, observation and documentation as a complementary method. The data analysis technique used is to use statistical analysis formulas. Based on the results of the study, rhitung processed larger than rtabel that is (1,497>0,497) which means the results of this study are